Challenges in the Pharmacotherapeutic Management of Pediatric Asthma - Ileana Ioniuc; Ingrith Miron; Vasile Valeriu Lupu; Iuliana Magdalena Starcea; Alice Azoicai; Monica Alexoae; Anca Adam Raileanu; Felicia Dragan; Ancuta Lupu (MDPI AG, 2022)
Bronchial asthma is one of the most common chronic conditions in pediatric practice, with increasing prevalence hampered by poor socioeconomic impacts, leading to major public health issues. Considered as a complex heterogeneous syndrome, not a single disease, the management of the disease is a real challenge, impacting medical staff, patients and caregivers. Over the decades, a significant number of diagnostic and treatment regimen have been developed to achieve good standards, sustaining balanced control of the disease. This paper attempts a review on the establishment of new trends in the management of bronchial asthma in the pediatric age group.